EPC Agenda 2004-05-06 - Academic Senate:::::::::
Educational Policies Committee. Chair Report. Agenda – Approved. Minutes of 12/13/19 – Approved. Consent item: Faculty Eligible for Emeritus status – Approved. President Report. Provost Report. Vice Chair Report. President's Climate Leadership Commitment Presentation. Discontinuance: Education concentration in TESOL – Approved. VP of Administration and Finance Report. VP of Student Affairs Report. Associated Students Report. Statewide Senator Report. Staff Rep Report. APARC Report. EPC Report. FSAC Report. SAC Report. CFA Report. Good of the Order